The species of Amanita mushroom at Haurbentes Research Forest, West Java - Oktan Dwi Nurhayat; Ivan Permana Putra (Foresty Faculty of Hasanuddin University, 2022)
Ectomycorrhizal fungi play an important role in a forest ecosystem. The genus of Amanita is one of the common ectomycorrhizal fungi in the forest. The information on the diversity of Amanita in Indonesia is not properly organized. This is due to most of the prior publications were not equipped with basidiomata descriptions. The current research aimed to inventory the diversity of Amanita and provide a description of the basidiomata from the Haurbentes Research Forest, West Java. Macrofungi exploration was carried out by the opportunistic sampling method and identification of fungi based on morphological characters. A total of seven species of Amanita were successfully described and identified in this study : Amanita sp.1, Amanita sp.2 sect. Vaginatae, Amanita sp.3 sect. Vaginatae, Amanita cf. alboflavescens, Amanita cf. virginea, Amanita cf. fulva and Amanita cf. sychnopyramis.This report is the first information of Amanita in research site and adds to the record of mushroom diversity in Indonesia.